Antibodies From Children With PANDAS Bind Specifically to Striatal Cholinergic Interneurons and Alter Their Activity - Xu, Jian; Liu, Rong-Jian; Fahey, Shaylyn; Frick, Luciana; Leckman, James; Vaccarino, Flora; Duman, Ronald S; Williams, Kyle; Swedo, Susan; Pittenger, Christopher (The American journal of psychiatry, 2021)
Objective:Pediatric obsessive-compulsive disorder (OCD) sometimes appears rapidly, even overnight, often after an infection. Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections, or PANDAS, describes such a situation after infection with Streptococcus pyogenes. PANDAS may result from induced autoimmunity against brain antigens, although this remains unproven. Pilot work suggests that IgG antibodies from children with PANDAS bind to cholinergic interneurons (CINs) in the striatum. CIN deficiency has been independently associated with tics in humans and with repetitive behavioral pathology in mice, making it a plausible locus of pathology. The authors sought to replicate and extend earlier work and to investigate the cellular effects of PANDAS antibodies on cholinergic interneurons.Methods:Binding of IgG to specific neurons in human and mouse brain slices was evaluated ex vivo after incubation with serum from 27 children with rigorously characterized PANDAS, both at baseline and after intravenous immunoglobulin (IVIG) treatment, and 23 matched control subjects. Binding was correlated with symptom measures. Neural activity after serum incubation was assessed in mouse slices using molecular markers and electrophysiological recording.Results:IgG from children with PANDAS bound to CINs, but not to several other neuron types, more than IgG from control subjects, in three independent cohorts of patients. Post-IVIG serum had reduced IgG binding to CINs, and this reduction correlated with symptom improvement. Baseline PANDAS sera decreased activity of striatal CINs, but not of parvalbumin-expressing GABAergic interneurons, and altered their electrophysiological responses, in acute mouse brain slices. Post-IVIG PANDAS sera and IgG-depleted baseline sera did not alter the activity of striatal CINs.Conclusions:These findings provide strong evidence for striatal CINs as a critical cellular target that may contribute to pathophysiology in children with rapid-onset OCD symptoms, and perhaps in other conditions.